1980
DOI: 10.1126/science.7367873
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Air Pollution, Tobacco Smoke, and Public Health

Abstract: An experimental and theoretical investigation is made into the range and nature of the exposure of the nonsmoking public to respirable suspended particulates from cigarette smoke. A model incorporating both physical and sociological parameters is shown to be useful in understanding particulate levels from cigarette smoke in indoor environments. Observed levels of particulates correlate with the predictions of the model. It is shown that nonsmokers are exposed to significant air pollution burdens from indoor sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
148
2
3

Year Published

1988
1988
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 293 publications
(157 citation statements)
references
References 30 publications
4
148
2
3
Order By: Relevance
“…At least for IHD there does not appear to be a difference in the magnitude of the association with passive smoking with respect to fatal and nonfatal outcome (200). Furthermore, the researchers made no attempt in the analyses to differentiate between exposure to environmental tobacco smoke at home, at work, or elsewhere, because exposure at work has been found to confer a greater risk from IHD than exposure at home (208,209). The study showed that nonsmokers exposed to environmental tobacco smoke have a significantly increased risk of stroke incidence and fatality among both men (OR 2.1, 95% CI 1.3-3.3) and women (OR 1.7, 95% CI 1.1-2.6) when compared with nonsmokers not exposed to environmental tobacco smoke.…”
mentioning
confidence: 99%
“…At least for IHD there does not appear to be a difference in the magnitude of the association with passive smoking with respect to fatal and nonfatal outcome (200). Furthermore, the researchers made no attempt in the analyses to differentiate between exposure to environmental tobacco smoke at home, at work, or elsewhere, because exposure at work has been found to confer a greater risk from IHD than exposure at home (208,209). The study showed that nonsmokers exposed to environmental tobacco smoke have a significantly increased risk of stroke incidence and fatality among both men (OR 2.1, 95% CI 1.3-3.3) and women (OR 1.7, 95% CI 1.1-2.6) when compared with nonsmokers not exposed to environmental tobacco smoke.…”
mentioning
confidence: 99%
“…The first publications on the adverse health effects of passive smoking in adults were published in the early 1980s. [34][35][36] By the 1990s, the evidence base had progressed to a critical point at which the EPA classified passive smoke as a Class A carcinogen. 2 The publications submitted by tobacco industry opponents of regulation were older, most from a period when less evidence on the adverse health effects of passive smoking existed.…”
Section: Discussionmentioning
confidence: 99%
“…These numbers led to the prediction that a typical office building should have mass concentrations between approximately 20 and 200 pg/m3 (Penkala and De Oliveira, 1975;Binder et al, 1976;Repace and Lowrey, 1980;Spengler et al, 1981;Quant et al, 1982).…”
Section: Introductionmentioning
confidence: 99%